Calculate ( 1 2 x 2 + 4 x − 5 7 ) 2 0 1 9 for x = 6 + 2 5 − 5 3 1 0 + 6 3 ( 3 − 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
After simplification we get x = 2 and the given quantity = − 1
How would you simplify this
Log in to reply
( 3 + 1 ) 3 = 1 0 + 6 3 , ( 3 + 1 ) ( 3 − 1 ) = 2 . 6 + 2 5 = 5 + 1 . So the numerator is 2 and the denominator is 1 , and x = 1 2 = 2
Problem Loading...
Note Loading...
Set Loading...
Given that x = 6 + 2 5 − 5 3 1 0 + 6 3 ( 3 − 1 ) = ( 1 + 5 ) 2 − 5 3 ( 3 + 1 ) 3 ( 3 − 1 ) = 1 + 5 − 5 ( 3 + 1 ) ( 3 − 1 ) = 1 2 = 2 .
Therefore ( 1 2 x 2 + 4 x − 5 7 ) 2 0 1 9 = ( 4 8 + 8 − 5 7 ) 2 0 1 9 = ( − 1 ) 2 0 1 9 = − 1 .